POST ISCHEMIC STROKE IMAGING AND ITS CLINICAL RELEVANCE: A SYSTEMATIC REVIEW - Amalia Amin, Assyifa (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Stroke is a focal or global functional brain disorder that starts suddenly and lasts longer than 24 hours and is caused by changes in cerebral blood flow. It is not caused by transient cerebral circulatory abnormalities, brain tumors, or secondary strokes as a result of trauma or infection. Strokes can develop in any part of the brain. Ischemia or brain hemorrhage are also potential causes of a stroke that occurs suddenly and leads in neurologic impairments. Strokes are classified into two types: bleeding and non-bleeding. Both are potentially fatal. Several studies have found that imaging is required before treating an acute ischemic stroke. The importance of imaging after stroke treatment, on the other hand, is less obvious. Bleeding, particularly cerebral haemorrhage, is the most feared complication in people who have had acute ischemic stroke treatment. As a result, the AHA/ASA IV-tPA guidelines recommend that a non-contrast computed tomography (NCCT) brain scan be performed at least 24 hours after therapy. Non-contrast CT (NCCT) is still the cheapest, quickest, most generally available, and simplest method for diagnosing intracerebral bleeding after an ischemic stroke. However, MRI with the right sequences may be able to detect the same thing. The NCCT may frequently detect hyperdense regions following treatment for acute ischemic stroke. Magnetic resonance imaging (MRI) is one of the most commonly used imaging methods both before and after stroke treatment due to the wealth of information it gives. Finally, post-ischemic stroke imaging is becoming increasingly essential because it can provide both specific clinical guidance and a better knowledge of the processes that occur after such a severe impact on the brain. It may aid in the prediction of long-term outcomes and, in the future, may assist clinicians in tailoring and optimizing rehabilitation efforts for specific patients.